Using Structural Equation Modelling to Assess factors that affect Reverse Supply Chain Implementation and its Impact on the Economic and Environmental Performance: Case of OEMs in the automotive sector in Morocco - EL OUELDRHIRI , Sara (Revue Internationale des Sciences de Gestion, 2022)
A structural equations modelling (SEM) was used to test the impact of five stakeholders and the manager posture’s on Reverse logistic (RL) implementation as well as relationships between RL and environmental/economic performance, Moreover, we also used a SEM to study the moderating effects of ISO 14001 certification between RL and environmental performance, as well as the moderating role of company size between RL and economic performances in a sample of 55 OEMs in the automotive sector of Morocco. Results suggest that government importance and RL are negatively linked. In regard to the other determinants of RL implementation, results showed that RL is positively linked to the importance of shareholders, customers, employees and the strategic stance of the manager. However, the importance of local community exercises no influence on the level of implementation of RL. In addition, this study concludes that RL can enhance environmental and economic performance. Moreover, our results showed that with the size of the company, RL increase the level of economic performance, moreover, the interaction between RL and certification is positively related to environmental performance.